PENDUKUNG KEPUTUSAN PEMILIHAN JURUSAN DI SMAN 2 PULAU PUNJUNG MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) BERBASIS WEB - Nori Sahrun; Radiyan Rahim (Institut Teknologi dan Bisnis (ITB) Swadharma, 2022)
Many methods can be used in decision-making systems. One of the methods used in this research is the Analytical Hierarchy Process (AHP) method. The concept of the AHP method is to change qualitative values into quantitative values. This decision support model will describe a complex multi-factor or multi-criteria problem into a hierarchy so that the decisions taken are usually more objective. The Decision Support System uses the web-based Analytical Hierarchy Process method to determine the department. This is a decision support system designed to determine the majors for grade X students at school 2 on Punjung island. The assignment that will be given is taken from various criteria such as the average score of report cards, understanding of the material, and student interests. With this application, it is hoped that students will get a department according to their respective interests and abilities. This system is made web-based using the programming languages PHP and MySQL and uses the Analytical Hierarchy Process (AHP) Decision Support System method